“More than Meets the Eye” - Analyzing the Success of User Queries in Oria - Hugo C. Huurdeman; Mikaela Aamodt; Dan Michael Heggø (Nordic Journal of Information Literacy in Higher Education, 2018)
Discovery systems allow academic library users to locate a wider range of resources than previous OPACs. However, actual usage of these systems may still be challenging. The main aim of this research is to get a better understanding of the hurdles users face while searching contemporary library systems.